EVALUASI PELAKSANAAN E-TENDERING PADA UNIT LAYANAN PENGADAAN DAERAH KEMENTERIAN KEUANGAN PROVINSI SULAWESI SELATAN - Yohanis Salupra (Politeknik STIA LAN Makassar, 2020)
The implementation of government procurement of goods / services through e-tendering in Indonesia is still experiencing several problems. As with the implementation of e-tendering at the Regional Procurement Service Unit of the Ministry of Finance of South Sulawesi Province, which experienced a failed tender. In 2016, the number of failed tenders was as many as six failed tender packages amounting to IDR 4,695,581,000.00. Then in 2017, the number of tender packages failed as many as four packages amounting to IDR 36,531,445,000.00. In 2018, four packages experienced failed tenders valued at IDR 23,407,124,000.00. Until August 2019, there were two failed tenders with a value of IDR 2,061,932,000.00. In addition, there are still suppliers' conspiracy to participate in tenders. This study aims to evaluate the implementation of E-Tendering at the Regional Procurement Service Unit of the Ministry of Finance of South Sulawesi Province using a qualitative descriptive approach through interviews, observation and documentation study. The results showed that there was a delay in the completion of the tender, and the implementation of the reverse auction was not in accordance with the provisions. Adequacy of costs and results in the implementation of e-tendering has been fulfilled and there is also an even distribution of activities and benefits for all parties directly involved in the e-tendering process. The satisfaction of the parties in implementing e-tendering is the ease of system access, open competition and processes, and the ability to reduce workloads. Network maintenance that interferes with the tender schedule, the fairness of the Pokja ULPD honorarium, and the process of providing an explanation are not in accordance with the provisions. The implementation of e-tendering at the Regional Procurement Service Unit of the Ministry of Finance of South Sulawesi Province has been carried out quite well but there are still several things that need to be addressed, including the ad hoc status of the ULPD Working Group, competency of the parties, coordination between PPK and Pokja ULPD, network maintenance, fairness of value. honorarium for Pokja ULPD, and implementation of the stages of giving explanations..